2016
DOI: 10.1038/srep38441
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dose reduction on bone strength prediction using finite element analysis

Abstract: This study aimed to evaluate the effect of dose reduction, by means of tube exposure reduction, on bone strength prediction from finite-element (FE) analysis. Fresh thoracic mid-vertebrae specimens (n = 11) were imaged, using multi-detector computed tomography (MDCT), at different intensities of X-ray tube exposures (80, 150, 220 and 500 mAs). Bone mineral density (BMD) was estimated from the mid-slice of each specimen from MDCT images. Differences in image quality and geometry of each specimen were measured. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 43 publications
1
22
0
Order By: Relevance
“…The whole femur CT scan protocol recommended by the CT2S service 4 involves an effective radiation dose in the range of 1.9–4.8 mSv for males and 1.3–3.2 mSv for females. A recent study on the effect of reducing the X-ray energy on the predictive accuracy of QCT-SSFE of vertebral bodies suggests that even more aggressive reductions can be adopted without any significant loss of predictive accuracy [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The whole femur CT scan protocol recommended by the CT2S service 4 involves an effective radiation dose in the range of 1.9–4.8 mSv for males and 1.3–3.2 mSv for females. A recent study on the effect of reducing the X-ray energy on the predictive accuracy of QCT-SSFE of vertebral bodies suggests that even more aggressive reductions can be adopted without any significant loss of predictive accuracy [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…Early, accurate, and efficient bone density assessment is mandatory to tailor and monitor the clinical treatment of, e.g., osteoporosis 5,6,47 . It has been shown that patient-specific FEA that utilizes QCT for material property identification is beneficial over DXA-based BMD measurement for diagnosis and medication effect assessment in osteoporotic patients 2,3,29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Anitha et al . showed that radiation dose (by tube exposure reduction) could be reduced to 64% with no impact on strength estimates obtained from finite-element- (FE-) analysis and no significant difference in volume quantification 32 . Evidence of the dose reduction potential of IR is also provided by other studies of musculoskeletal CT: Geravaise et al .…”
Section: Discussionmentioning
confidence: 99%